Product Innovation, Customer Satisfaction, and Brand Loyalty of Using Smartphones Among University Students : PLS – SEM Approach - Panigrahi, Shrikant Krupasindhu; Azizan, Noor Azlinna Binti; Al Shamsi, Ibrahim Rashid (Indian Journal of Marketing, 2021)
This paper examined the impact of product innovation attributes (relative advantage, complexity, compatibility, trialability, and observability) on customer satisfaction and brand loyalty together with gender as a moderator between customer satisfaction and brand loyalty. Based on a sample of 193 university students using partial least square structural equation modeling (PLS-SEM) technique, relative advantage, complexity, compatibility, trialability, and observability were found to positively impact customer satisfaction. The results also demonstrated that product innovation attributes were the key predictors of customer satisfaction. The results revealed that loyal customers utilized the services of specific smartphones as per their preferences consistently. Additionally, the results illustrated that customer satisfaction significantly influenced brand loyalty. Further, the study also found that gender significantly moderated customer satisfaction and brand loyalty. As a practical implication, in the competitive market, the managers need to understand the requirements of the customers and add value to customers by providing innovative products. Innovation in a product improves customer satisfaction and commitment of customers towards a brand. Managers need to understand the requirement of the customers and create value accordingly. As a novelty, the study is a first of its kind to investigate the relationship between product innovation attributes, customer satisfaction, and brand loyalty with gender as a moderator.